NFIX Regulates Neural Progenitor Cell Differentiation During Hippocampal Morphogenesis. (4th October 2012) - Heng, Yee Hsieh Evelyn; McLeay, Robert C.; Harvey, Tracey J.; Smith, Aaron G.; Barry, Guy; Cato, Kathleen; Plachez, Céline; Little, Erica; Mason, Sharon; Dixon, Chantelle; Gronostajski, Richard M.; Bailey, Timothy L.; et al.
Abstract : Neural progenitor cells have the ability to give rise to neurons and glia in the embryonic, postnatal and adult brain. During development, the program regulating whether these cells divide and self-renew or exit the cell cycle and differentiate is tightly controlled, and imbalances to the normal trajectory of this process can lead to severe functional consequences. However, our understanding of the molecular regulation of these fundamental events remains limited. Moreover, processes underpinning development of the postnatal neurogenic niches within the cortex remain poorly defined. Here, we demonstrate that Nuclear factor one X (NFIX) is expressed by neural progenitor cells within the embryonic hippocampus, and that progenitor cell differentiation is delayed within Nfix −/− mice. Moreover, we reveal that the morphology of the dentate gyrus in postnatal Nfix −/− mice is abnormal, with fewer subgranular zone neural progenitor cells being generated in the absence of this transcription factor. Mechanistically, we demonstrate that the progenitor cell maintenance factor Sry-related HMG box 9 (SOX9) is upregulated in the hippocampus of Nfix −/− mice and demonstrate that NFIX can repress Sox9 promoter-driven transcription. Collectively, our findings demonstrate that NFIX plays a central role in hippocampal morphogenesis, regulating the formation of neuronal and glial populations within this structure.